Job-sharing cathode design for Li–O2 batteries with high energy efficiency enabled by in situ ionic liquid bonding to cover carbon surface defects. Issue 1 (1st December 2015) - Lou, Peili; Li, Chilin; Cui, Zhonghui; Guo, Xiangxin
Abstract : In the job-sharing design of carbon-based cathode for Li–O2 batteries, the IL layer is aimed to cover carbon surface defects and suppress side reactions, whereas Ru nanodots are responsible for modifying product microstructure and crystallinity. It enables a high energy efficiency characterized by a substantial charge plateau with extremely small overpotential. Abstract : The difficult achievement of high round-trip energy efficiency or low charge overpotential has retarded Li–O2 (air) batteries in real applications. Although much effort has been focused on exploring novel catalysts, their potential effects are usually counteracted by a quick passivation of the electrode as a consequence of side reactions, which likely contribute to the widely observed high-voltage reversibility ( e.g. >4 V). Here, we report a job-sharing design of a carbon-based cathode, Ru-IL (ionic liquid)–CNT (carbon nanotube), with fine Ru nanodots anchored on the IL-decorated CNT surface. The subnanometer IL cation linker is crucial to seal carbon surface defects without sacrificing Li + /e − charge transfer and therefore efficiently suppresses the occurrence of side reactions. This charged decoration guarantees that Ru functions as the microstructure promoter to stabilize highly disordered Li2 O2 . It enables achievement of high energy efficiency (80–84%) Li–O2 batteries characterized by a substantial charge plateau with an extremely low overpotential of 0.18 V. Even by using the mode of voltage cut-off, a reversible capacity around 800–1000 mA h g −1 is maintained for more than 100 cycles. When the reversible capacity is limited to 500 mA h g −1, the cycling number can reach up to at least 240 cycles. The disentangled CNT networks, loose precipitation of nanostructured products and high donor number electrolytes allow thick electrode fabrication (8 mg cm −2 ), leading to a high areal capacity of 3.6–7.6 mA h cm −2 . Our results indicate a defect-inspired strategy to bury undesired defect sites in the original electrode framework and to electrochemically synthesize the stable defect-rich Li2 O2 product.